Trends and Digital Innovation: Analyzing the Impact of E-Commerce and Social Media on the Growth of Handicraft MSMEs - Guspian, Iza; Zahri, Tsulis Amiruddin (STMIK Banjarbaru, 2025)
Handicraft MSMEs in Belitung Regency face challenges in adopting digital technology, even though their products have high cultural value. This study analyzes the use of e-commerce and social media by MSMEs to market their products and explores support that can increase digital capacity, such as digital literacy training and infrastructure improvements. The methods used include interviews with local handicraft MSME practitioners and a systematic review using PRISMA analysis. The results show that digitalization opens up opportunities to expand markets and increase income, but obstacles such as low digital literacy, limited internet connectivity, and global competition are still significant. Therefore, a strategy is needed that integrates the use of technology with increasing human resource capacity and infrastructure. These findings provide input for stakeholders, entrepreneurs, and policy makers to support the growth of handicraft MSMEs through sustainable and inclusive digital transformation.Keywords: Micro Small and Medium Enterprises; Handicrafts; E-commerce; Social media; Digital innovation. AbstrakUsaha Mikro Kecil dan Menengah (UMKM) kerajinan tangan di Kabupaten Belitung menghadapi tantangan dalam mengadopsi teknologi digital, meskipun produk mereka memiliki nilai budaya tinggi. Penelitian ini menganalisis pemanfaatan e-commerce dan media sosial oleh UMKM untuk memasarkan produk serta mengeksplorasi dukungan yang dapat meningkatkan kapasitas digital, seperti pelatihan literasi digital dan perbaikan infrastruktur. Metode yang digunakan meliputi wawancara dengan pelaku UMKM lokal dan kajian sistematis menggunakan analisis PRISMA. Hasil menunjukkan bahwa digitalisasi membuka peluang memperluas pasar dan meningkatkan pendapatan, namun hambatan seperti rendahnya literasi digital, konektivitas internet yang terbatas, dan persaingan global masih signifikan, sehingga diperlukan strategi yang mengintegrasikan pemanfaatan teknologi dengan peningkatan kapasitas sumber daya manusia dan infrastruktur. Temuan penelitian ini memberikan masukan bagi pemangku kepentingan, pengusaha, dan pembuat kebijakan untuk mendukung pertumbuhan UMKM kerajinan tangan melalui transformasi digital yang berkelanjutan dan inklusif.Kata Kunci: Usaha Mikro Kecil dan Menengah; Kerajinan Tangan; E-commerce; Media Sosial; Inovasi Digital.